Unraveling the Big Sleep: Molecular Aspects of Stem Cell Dormancy and Hibernation - Dias, Itamar B.; Bouma, Hjalmar R.; Henning, Robert H. (Frontiers in Physiology, 2021)
Tissue-resident stem cells may enter a dormant state, also known as quiescence, which allows them to withstand metabolic stress and unfavorable conditions. Similarly, hibernating mammals can also enter a state of dormancy used to evade hostile circumstances, such as food shortage and low ambient temperatures. In hibernation, the dormant state of the individual and its cells is commonly known as torpor, and is characterized by metabolic suppression in individual cells. Given that both conditions represent cell survival strategies, we here compare the molecular aspects of cellular quiescence, particularly of well-studied hematopoietic stem cells, and torpor at the cellular level. Critical processes of dormancy are reviewed, including the suppression of the cell cycle, changes in metabolic characteristics, and cellular mechanisms of dealing with damage. Key factors shared by hematopoietic stem cell quiescence and torpor include a reversible activation of factors inhibiting the cell cycle, a shift in metabolism from glucose to fatty acid oxidation, downregulation of mitochondrial activity, key changes in hypoxia-inducible factor one alpha (HIF-1α), mTOR, reversible protein phosphorylation and autophagy, and increased radiation resistance. This similarity is remarkable in view of the difference in cell populations, as stem cell quiescence regards proliferating cells, while torpor mainly involves terminally differentiated cells. A future perspective is provided how to advance our understanding of the crucial pathways that allow stem cells and hibernating animals to engage in their ‘great slumbers’.